Profitability and resource use efficiency in vegetable cultivation in Haryana: Application of Cobb-Douglas production model - KUMAR, AJAY; ROHILA, ANIL KUMAR; PAL, VIJAY KUMAR (The Indian Journal of Agricultural Sciences, 2018)
Vegetable cultivation plays an important role in the agricultural economy of India. Small and marginal farmers of India grow vegetable for generating income and increasing nutrient in the diet of people. But limited research was done on profitability and resource use efficiency of potato and tomato which are the major vegetable crops grown by farmers in Haryana. Study was carried out in 2014-15 on the basis of primary data to know costs, returns and resource use efficiency of potato and tomato cultivation. The purposive sampling was used to select districts and villages on the basis of highest area under these crops. Probability proportion to size method was used to select the 60 farmers and categorized under small, medium and large farmers. Study concluded that rupee investment in potato and tomato cultivation was 1.40 and 2.09, respectively which was highest to medium farm category in both the vegetable crops and indicated that medium farms are more efficient and have more economies of scale due to better management practices, sound financial position and efficient use of resources. Farm yard manure (FYM) resource has significantly positive impact whereas irrigation was significantly negative impact on yield of potato. However, seeds, machine labour and weeding have positive impact whereas human labour was significantly negative impact on yield of tomato.